Democracy and the Presidential Function in Francophone Black Africa : the case of Bénin, Ivory Coast, Mali and Togo - (:unkn) unknown (My University, 2016)
With the new African constitutionalism of the 1990's the French speaking elements of black Africa signal a rupture with the ancient practices of rising to power leading to a rearrangement of modalities to attain the presidential function through free and competitive elections. They consecrate to the alternation power by foreseeing the modalities of terminating their function as acting president of the Republic including the limitative clause of presidential mandates which leads to great controversy. They will make public their desire to reduce the power of the president of the Republic through the executive dicephalic institution and the creation of legislative and jurisdictional counter powers. This is doomed to fail since the president of the Republic will, regardless of everything, manage to be the only master of the executive power, the only master of the national politics and administration. Furthermore, from now on we will see certain presidents of the Republics make use of constitutional fiddling and electoral fraud to keep their position; and the armed forces will resort more to a putsch to take hold of power, which will lead to reactions from the international Community. This fact can be explained by the fact that, in Africa, the function of president of the Republic is a function linked to political and sociological apprehension at the antipode of liberal democracy. This will make such a function become one more function out of the control of the constitution.
Keywords: African Research